Twelve years of rabies surveillance in Sri Lanka, 1999-2010. - Dushantha Karunanayake; Takashi Matsumoto; Omala Wimalaratne; Susilakanthi Nanayakkara; Devika Perera; Akira Nishizono; Kamruddin Ahmed (Public Library of Science (PLoS), 2014)
Rabies is endemic in Sri Lanka, but little is known about the temporal and spatial trends of rabies in this country. Knowing these trends may provide insight into past control efforts and serve as the basis for future control measures. In this study, we analyzed distribution of rabies in humans and animals over a period of 12 years in Sri Lanka.Accumulated data from 1999 through 2010 compiled by the Department of Rabies Diagnosis and Research, Medical Research Institute (MRI), Colombo, were used in this study.The yearly mean percentage of rabies-positive sample was 62.4% (47.6-75.9%). Three-fourths of the rabies-positive samples were from the Colombo, Gampaha, and Kalutara districts in Western province, followed by Galle in Southern province. A high percentage of the rabies samples were from dogs (85.2%), followed by cats (7.9%), humans (3.8%), wild animals (2.0%), and livestock (1.1%). Among wild animals, mongooses were the main victims followed by civets. The number of suspect human rabies cases decreased gradually in Sri Lanka, although the number of human samples submitted for laboratory confirmation increased.The number of rabid dogs has remained relatively unchanged, but the number of suspect human rabies is decreasing gradually in Sri Lanka. These findings indicate successful use of postexposure prophylaxis (PEP) by animal bite victims and increased rabies awareness. PEP is free of charge and is supplied through government hospitals by the Ministry of Health, Sri Lanka. Our survey shows that most positive samples were received from Western and Southern provinces, possibly because of the ease of transporting samples to the laboratory. Submissions of wild animal and livestock samples should be increased by creating more awareness among the public. Better rabies surveillance will require introduction of molecular methods for detection and the establishment of more regional rabies diagnostic laboratories.